1981
DOI: 10.3109/15563658108990285
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Efficacy of Gastric Lavage as Practiced in a Large Metropolitan Hospital

Abstract: The efficacy of gastric lavage as it is practiced in a major metropolitan hospital was evaluated. From a population of 76 patients with chemical evidence of sedative-hypnotic drugs in the blood, two or more therapeutic doses were recovered from 15.8% of the lavage samples, and 10 or more therapeutic doses were recovered from 6.6%. In a population consisting of patients with detectable quantities of drugs in the lavage sample, diazepam and amitriptyline are more adequately recovered than the sedative-hypnotic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

1984
1984
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 15 publications
1
17
0
1
Order By: Relevance
“…In early trials looking at the recovery of drugs, usually barbiturates, from gastric washings the amount of drug recovered was low and in a significant proportion of patients no drug was recovered at all (Harstad et al, 1942, Allan, 1961Matthew et al, 1966). Better results have been reported with other drugs with amounts equivalent to 10 therapeutic doses recovered in 50% of patients ingesting salicylate (Matthew et al, 1966) and 33% of patients ingesting amitriptyline (Comstock et al, 1981). When gastric lavage is compared to emesis by measuring the recovery of administered markers it appears that lavage is more effective (Auerbach et al, 1986, Tanberg et al, 1986.…”
Section: Discussionmentioning
confidence: 92%
“…In early trials looking at the recovery of drugs, usually barbiturates, from gastric washings the amount of drug recovered was low and in a significant proportion of patients no drug was recovered at all (Harstad et al, 1942, Allan, 1961Matthew et al, 1966). Better results have been reported with other drugs with amounts equivalent to 10 therapeutic doses recovered in 50% of patients ingesting salicylate (Matthew et al, 1966) and 33% of patients ingesting amitriptyline (Comstock et al, 1981). When gastric lavage is compared to emesis by measuring the recovery of administered markers it appears that lavage is more effective (Auerbach et al, 1986, Tanberg et al, 1986.…”
Section: Discussionmentioning
confidence: 92%
“…Gastric lavage is rarely used in acute overdoses of medication, and is typically performed using a 30 French orogastric tube. In experimental animal studies, lavage may decrease absorption by 26% to 37% [48][49][50][51]; however, human studies have not demonstrated a consistent effect on patient outcome [52][53][54]. Due to significant evidence of morbidity including aspiration, laryngospasm, and esophageal perforation [55], lavage should not be used unless the GI toxin is life threatening and the procedure can be completed within 1 hour of ingestion [55].…”
Section: Gastrointestinal Decontaminationmentioning
confidence: 99%
“…More recent experience with barbiturates merely serves to confirm that gastric lavage only retrieves large amounts in a minority of those treated. Comstock et al (1981) recovered more than two therapeutic doses in 13-9% of poisonings with short-acting barbiturates and 22-7% with phenobarbitone. However, only five patients surrendered between 11 and 20 therapeutic doses.…”
Section: Does Gastric Lavage Really Recover Poison?mentioning
confidence: 99%
“…Matthew et al (1966) considered more than 200 mg of a barbiturate was enough while Comstock et al (1981) regarded two therapeutic doses as success. But by any standard these are small amounts and whether their recovery in borderline cases would weight the scales in favour of survival or reduced morbidity by the time patients reach hospital must be open to serious doubt.…”
Section: Does Gastric Lavage Really Recover Poison?mentioning
confidence: 99%